The role of cost-effectiveness analysis in the development of indicators to support incentive-based behaviour in primary care in England - Qureshi, Nadeem; Weng, Stephen; Hex, Nick (Sage, 2016)
In England, general practitioners are incentivized through a national pay-for-performance scheme to adopt evidence-based quality improvement initiatives using a portfolio of Quality and Outcomes Framework (QOF) indicators. We describe the development of the methods used to assess the cost-effectiveness of these pay-for-performance indicators and how they have contributed to the development of new indicators. Prior to analysis of new potential indicators, an economic subgroup of the National Institute for Health and Care Excellence (NICE) Indicator Advisory Committee is formed to assess evidence on the cost-effectiveness of potential indicators in terms of the health benefits gained, compared to the cost of the intervention and the cost of the incentive. The expert subgroup is convened to reach consensus on the amounts that could potentially be paid to general practices for achieving new indicators. Indicators are also piloted in selected general practices and evidence gathered about their practical implementation. The methods used to assess economic viability of new pilot indicators represent a pragmatic and effective way of providing information to inform recommendations. Current policy to reduce QOF funding could shift the focus from national (QOF) to local schemes, with economic appraisal remaining central.